Additions to the description of the fanworm genus Pseudofabricia Cantone, 1972 (Polychaeta: Sabellidae: Fabriciinae) - Fitzhugh, K. (Contributions in Science, Los Angeles, 1995)
The monotypic genus Pseudofabricia Cantone, 1972, with type species P. aberrans, was originally described from two specimens, both of which lacked branchial crowns. Neither of these specimens was, however, formally designated as a type. Only one of these specimens is extant. That specimen is redescribed and designated as the lectotype and is compared to some of the complete specimens used by Giangrande and Cantone (1990) in their redescription of the taxon. These latter specimens have nonvascularized ventral filamentous appendages in the branchial crown, which appear to be homologous to those in Fabriciola Friedrich, yet differ in that they are only slightly longer than the dorsal lips. Contrary to what was described by Giangrande and Cantone, the manubria of abdominal uncini in P. aberrans are about the same lengrh as the dentate region. Based on the present redescription, the cladistic relationships of Pseudofabricia to other fabriciin taxa are discussed.
Kristian Fauchald's Polychaeta DB